2007
DOI: 10.1074/jbc.m610544200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Non-lysosomal Glucosylceramidase as β-Glucosidase 2

Abstract: The primary catabolic pathway for glucosylceramide is catalyzed by the lysosomal enzyme glucocerebrosidase that is defective in Gaucher disease patients. A distinct non-lysosomal glucosylceramidase has been described but its identity remained enigmatic for years. We here report that the non-lysosomal glucosylceramidase is identical to the earlier described bile acid ␤-glucosidase, being ␤-glucosidase 2 (GBA2). Expressed GBA2 is identical to the native non-lysosomal glucosylceramidase in various enzymatic featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(192 citation statements)
references
References 28 publications
9
178
0
5
Order By: Relevance
“…Additionally, we provide evidence for impairment of T-cell maturation and egress of mature thymocytes in advanced GD. This prompts us to determine whether dense Gaucher cell infiltration in the thymus, as described hitherto, as well as in human GD (39), leads to elevated local concentrations of LysoGL1 and of sphingosine, thereof, via the action of neutral glucocerebrosidase, GBA2 (40,41). In this scenario, the abolition of sphingosine-1-phosphate gradient could be envisioned to block lymphocyte egress from the thymus (42).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, we provide evidence for impairment of T-cell maturation and egress of mature thymocytes in advanced GD. This prompts us to determine whether dense Gaucher cell infiltration in the thymus, as described hitherto, as well as in human GD (39), leads to elevated local concentrations of LysoGL1 and of sphingosine, thereof, via the action of neutral glucocerebrosidase, GBA2 (40,41). In this scenario, the abolition of sphingosine-1-phosphate gradient could be envisioned to block lymphocyte egress from the thymus (42).…”
Section: Discussionmentioning
confidence: 94%
“…glucose and ceramide as well as the reverse reaction consisting in the transfer of glucose to different lipid substrates [20,21]. The location of the missense variant, the high the family all together point toward a functional relevance of the p.Gly683Arg missense change to the pathogenesis.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…The enzyme, sensitive to CBE, is exclusively present in the microvilli of intestinal epithelial cells and possibly functions as a kind of digestive enzyme. Very recently, two research groups reported an alternative pathway (8,9), the catabolism of GlcCer by ␤-glucosidase 2 (GBA2), which has been known as a bile acid ␤-glucosidase (10). The enzyme, relatively nonsensitive to CBE, seems to be a membranebound enzyme of the ER (8) or located at or close to the cell surface (9).…”
Section: Glucosylceramide (Glccer)mentioning
confidence: 99%